International portfolio optimization based on uncertainty theory. (1st February 2021) - Huang, Xiaoxia; Wang, Xuting
ABSTRACT: This paper employs a new theory, i.e. uncertainty theory, to discuss an international portfolio investment in such a situation where the future security prices and the foreign exchange rates are evaluated by experts instead of historical data and are regarded as uncertain variables. First, an uncertain mean–chance model for international portfolio selection is proposed. For further discussion, the deterministic equivalent forms of the model are presented. Then we give the analytical solution of the model. Furthermore, the impact of forward hedging on uncertain international portfolio investment is discussed through the comparison of the international portfolio investment unhedged by forward contracts with that hedged by forward contracts. At small risk tolerable level, forward contracts have a good performance in hedging risk and bring high return. But, when the risk tolerable level becomes large, the risk reduction caused by the forward contracts also eliminates the potential high return. Moreover, considering forward in international portfolio can bring more stable and relatively high return than that no forwards are considered. And no forward contracts investment also has the opportunity to obtain higher returns than that considering forward investments.